(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
In this article, in the first years of the new economic policy in the Autonomous Republic of Turkestan, the number of poor peasants among the rural population decreased somewhat. As mentioned above, market relations had a positive effect on this, and on the other hand, the land reform of 1921-22 had a positive effect. During these years, the weight of middle-class farmers increased significantly.